Toleransi Keberagamaan Sekte Ibâdîyah Era Dinasti Rustamîyah - Rofiq, Ahmad Choirul (Program Pascasarjana UIN Sunan Ampel Surabaya, 2013)
Similar to any theological sect, the Kharijite has split into many smaller groups. Usually all these groups were characterized as extreme factions who used violence in the pursuit of their purposes. However, the factual evidence proved that there was Ibadite which was considered as the most moderate group. The Ibadites tend to avoid extreme behaviour. Due to their moderation, they successively ascended to power. The example of their remarkable achievement was the Rustamid Dynasty in Maghreb from 160-296H (776-909AD). As far as the research is concerned, unfortunately, there is no comprehensive records on the Rustamid accomplishment. The Rustamids reigned their plural society with different backgrounds in ethnicity, nationality, and religion. By doing so, the Rustamids could generate harmonious life in the entire territory under their government. Besides, the Rustamids have achieved an extraordinary civilization. The Rustamid tolerance was based on their ideology. The moderate Ibadite doctrine inspired the Rustamids to become tolerant to their various people. Actually, Indonesians with their diversity could also achieve high civilization such as what the Rustamid has achieved in terms of religious tolerance.